The Relationship Between Academic Supervision and School Leadership Roles with Teacher Learning Innovation in the Implementation of the Merdeka Curriculum at Senior High Schools in Reteh District - Susi Susanti; Neni Hermita; Azhar Azhar (FKIP - Universitas Riau, 2026)
This study aims to determine the relationship between academic supervision and school leadership roles with teacher learning innovation in the implementation of the Merdeka Curriculum in high schools in Reteh District. This study uses a quantitative approach with a survey method. Data were collected by distributing questionnaires to 50 teachers from several high schools in Reteh District who were randomly selected as respondents. The data analysis technique used was multiple linear regression to test the extent of the independent variables. The analysis was conducted with the help of statistical programs to ensure the validity and reliability of the data. The results showed that academic supervision had a positive and significant relationship with teacher learning innovation in the implementation of the Merdeka Curriculum, with a regression coefficient value of 0.297. This means that every one-unit increase in academic supervision will increase teacher learning innovation by 0.297 units. This finding confirms the importance of the role of principals and supervisors in providing guidance, direction, and follow-up on classroom learning so that teachers are encouraged to continue to innovate. Thus, it can be concluded that improving the quality of academic supervision and school leadership is the key to encouraging teacher learning innovation in the era of the Merdeka Curriculum implementation.